A detailed analysis of the mechanism of a carbocationic triple shift rearrangement. Issue 15 (21st April 2015) - Ortega, Daniela E.; Gutiérrez-Oliva, Soledad; Tantillo, Dean J.; Toro-Labbé, Alejandro
<x xml:space="preserve">Abstract</x> The mechanism of a carbocationic triple shift rearrangement is analyzed within the conceptual framework of the reaction force.